The Automobile Girls in the Berkshires; Or, The Ghost of Lost Man's Trail - Crane, Laura Dent (Salt Lake City, UT : Project Gutenberg, 2008)
"The Automobile Girls in the Berkshires; Or, The Ghost of Lost Man's Trail" by Laura Dent Crane is a children's adventure novel written in the early 20th century. The story follows a group of girls known as "The Automobile Girls," who embarked on various escapades, this time venturing into the scenic Berkshires. Central to the plot are the sisters Barbara and Mollie Thurston, alongside their friends, as they encounter thrilling experiences amidst the natural beauty and mystery of the woods. The opening of the story introduces Barbara and Mollie as they explore the New Jersey woods, with Barbara expressing concern over their dire situation of being lost. Their playful banter reveals their personalities$1 (BMollie being carefree and optimistic, while Barbara's worries hint at deeper issues regarding their family's finances and her ambitions for the future. A sudden accident results in Barbara spraining her ankle, leading to a series of events where their friend Ruth unexpectedly appears, providing assistance. The beginning sets the stage for friendship, mystery, and adventure, hinting at the challenges the girls will face as they enter the Berkshires and encounter the potential supernatural elements tied to the "Ghost of Lost Man's Trail." (This is an automatically generated summary.)s
Release date is 2008-06-16
E-text prepared by Roger Frank and the Project Gutenberg Online Distributed Proofreading Team (https://www.pgdp.net)
Keywords: Adventure and adventurers -- Juvenile fiction; Girls -- Societies and clubs -- Juvenile fiction; Airships -- Juvenile fiction; Berkshire Hills (Mass.) -- Juvenile fiction; Automobile travel -- Juvenile fiction; Horses -- Juvenile fiction